(untitled) (Current Problems in Rail Vehicles, 2025)
The presented research highlights the analysis of the strength of an open wagon body when it is lifted to change bogies in the conditions of a railway ferry station. It has been established that the strength of the open wagon body structure withstands the loads arising during its lifting by a handling machine. There were analysed the places, where a transport equipment interacts with the towing brackets, which are welded to the corner posts of the wagon body. The conducted research will contribute to the creation of recommendations for the design of modern freight wagon structures and increasing the efficiency of the operation in railway-ferry stations.